A novel engineering process for spatial opto-mechatronic applications - Franke, Jörg; Zeitler, Jochen; Reitberger, Thomas (CIRP Annals - Manufacturing Technology, 2016)
Well-known advantages of optical data communication, like high-speed data transmissions and higher integration densities, are the main drivers for novel applications in the field of opto-electronics. A new innovative approach is to print polymer optical waveguides on spatial circuit carriers. This allows creating highly integrated devices that unify the characteristics of electro-optical circuits with the advantages of 3D-mechatronic integrated devices (MID). This paper describes the introduction of a novel engineering method that includes technology-specific processes for creating new spatial optomechatronic applications with the focus on printing technologies and computer-aided design.
Keywords: MID; optics; design; engineering; Aerosol-Jet printing; waveguide; manufacturing; opto-electronics

Ansatz zur integrativen Entwicklung räumlicher optomechatronischer Baugruppen - Zeitler, Jochen; Fischer, Christian; Franke, Jörg (Wissenschafts- und Industrieforum Intelligente Technische Systeme, 2015)
Keywords: MID; Optik; CAD; Design

Approach for the production chain of printed polymer optical waveguides–an overview - Loosen, Florian; Backhaus, Carsten; Zeitler, Jochen; Hoffmann, Gerd-Albert; Reitberger, Thomas; Lorenz, Lukas; Lindlein, Norbert; Franke, Jörg; Overmeyer, Ludger; Suttmann, Oliver; Wolter, Klaus-Jürgen; Bock, Karlheinz (Applied Optics, 2017)
Research for new production chains in the field of waveguide fabrication is a challenging task. Realizing a cost efficient manufacturing process allows integrating optical data communication in arbitrary structures, for example, the wing of an airplane or the body of a car. The production chain described in this paper contains the design, simulation, and fabrication process of printed polymer optical waveguides (POWs).

Automated reasoning and knowledge inference on OPC UA information models - Bakakeu, Jupiter; Brossog, Matthias; Zeitler, Jochen; Franke, Jörg; Tolksdorf, S.; Klos, H.; Peschke, J. (Proceedings - 2019 IEEE International Conference on Industrial Cyber Physical Systems, ICPS 2019, 2019)
The fourth industrial revolution demands flexibility, adaptability, transparency and semantic interoperability. Within the German Industry 4.0 initiative, the Reference Architecture Model Industrie 4.0 (RAMI4.0) has recently been standardized and OPC Unified Architecture (OPC UA) is listed as the sole recommendation for implementation of a communication layer. Even though OPC UA helps bridge the interoperability gap at the automation level, its semantic has not yet been formally defined and an efficient automated reasoning and knowledge inference on the OPC UA address space is therefore not yet possible. This paper addresses this issue by presenting a solution to infer knowledge from OPC UA information models. By analyzing and comparing the semantic expressiveness of the OPC UA address space with semantic knowledge representation formalisms such as RDF and OWL, we derived and implemented a solution to transform an OPC UA information model into an RDF-Graph expressing an OWL Ontology. Using the generated ontology, we were able to run a true reasoning task directly on the OPC UA address space. In this paper, the developed approach is conveniently validated on various case studies involving online factory reconfiguration, intelligent energy management, and human-machine interfaces.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Industrie 4.0; Knowledge Inference; OPC UA; Sementic Web; SPARQL.

Beeinflussung der optischen Eigenschaften von Polymer Optischen Wellenleitern durch das Druckpfad-Design - Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (DGaO Proceedings, 2019)
In der DFG-finanzierten Forschergruppe OPTAVER (Optische Aufbau- und Verbindungstechnik für baugruppenintegrierte Bussysteme) wurden erfolgreich Lichtwellenleiter mittels eines Aerosol-Druck-Verfahrens mit vorheriger Konditionierung hergestellt sowie ein virtuelles Abbild der gesamten Prozesskette erstellt. Dieses Verfahren ermöglicht nahezu beliebige Druckpfade, sodass dies den Weg frei macht für neue Realisationen von optischen Buskopplungen.Ein nun möglicher Druckpfad ist jedoch nicht zwangsweise eine Verbesserung in Bezug auf die optischen Eigenschaften des Lichtwellenleiters. Die besondere Geometrie des Querschnitts der Polymer Optischen Wellenleiter (POW) beeinflusst das Design des Druckpfades. Ein Beispiel dafür ist der minimale Radius, den eine Kurve haben darf, damit kein Licht aus dem Wellenleiter auskoppelt. Um nun Vorschriften für das Druckpfad-Design ableiten zu können, benötigt es einer Charakterisierung der POWs bezüglich verschiedenster Druckpfade. Diese Charakterisierung wird vorgestellt und die daraus abgeleiteten Druckpfad-Design Vorschriften aufgezeigt. Des Weiteren werden neue Realisierungsmöglichkeiten von optischen Buskopplungen vorgestellt
Keywords: Additive Fertigung; Polymer Optische Wellenleiter; optische Eigenschaften

Computer-Aided Design and Simulation of Spatial Opto-Mechatronic Interconnect Devices - Zeitler, Jochen; Reichle, Andreas; Franke, Jörg; Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert (26th CIRP Design Conference, 2016, 2016)
Optical technologies become increasingly important in modern sensor and communication applications. Nevertheless, manufacturing and design methods in the field of spatial opto-electronics have not been investigated intensively yet. A new approach is to print polymer waveguides on spatial carriers to use the full design freedom of opto-mechatronic assemblies. Up to now, no specific design tools and validation methods are available. The article describes possible technology-specific methods for designing spatial opto-mechatronic applications with the focus on computer-aided design (CAD) and raytracing simulation of spatial waveguides.
Keywords: computer-aided design (CAD); design method; optical communication; opto-electronics; simulation

Computer-Aided Design of Electro-Optical Assemblies - Zeitler, Jochen; Franke, Jörg (Springer International Publishing, 2022)
The integration of the different engineering disciplines in an integrated development procedure is the core of this chapter. For this purpose, the physical and technological principles of optical technologies must be considered. Product development methods of technical systems are a related field, since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these must be evaluated and expanded with regard to the new optomechatronic components. A separate procedure that differs from conventional development methods is just as important as the challenges that must be placed on modeling systems, the designer and the production of the 3D-Opto-MID. From these defined requirements, it was possible to derive a concept for a 3D optomechatronics CAD software (OMCAD) which contains the essential steps for creating these products.
CRIS-Team Scopus Importer:2024-12-16

Concepts for the design and optimization process of printed polymer-based optical waveguides (scattering processes) - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Proceeding, 4th doctoral students conference on optics (DoKDoK), 2015)

Design and simulation rules for printed optical waveguides with implemented scattering methods in CAD and raytracing software - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Proceeding, 117. DGaO-Jahrestagung, 2016)
The printing process of polymer optical waveguides is a new and uncharted research topic, which the research group OPTAVER is principally involved in. A main consequence of the printing process is the roughness of the interface between core and cladding. This surface between the dielectric media creates scattering in printed waveguides. To simulate this behaviour, standard non-sequential raytracing methods have to be extended with scattering algorithms. Here, scattering power spectra for each incident ray interacting with the rough surface are generated using the perturbation theory. Another task is to connect MID-speciﬁc CAD tools with raytracing simulations to create a holistic tool for design and validation of light propagation. This tool is specifically prepared to analyze the manufacturing process of polymer optical waveguides. This technique facilitates new applications in different research and development fields. Comparing the performances of real printed and simulated polymer optical waveguides is one of the major links between the different researchers of this DFG research group.
Keywords: Optisches Design; Optische Systeme; Optische Informationsübertragung

Engineering von mechatronischen Baugruppen für die additive Fertigung - Zeitler, Jochen; Kühn, Cornelius; Urban, Nikolaus; Franke, Jörg (Konstruktion, 2017)
Als Reaktion auf den wachsenden Einfluss der Mechatronik auf die Industrie ist die additive Fertigung inzwischen so weit entwickelt, dass sie dazu in der Lage ist, die Bedürfnisse von räumlichen, hochintegrierten und interdisziplinären Baugruppen zu erfüllen. In Form eines hybriden, rein additiven Fertigungsprozesses können sowohl mechanische Substratkörper, elektrisch leitfähige Strukturen, sowie Inlets, die während des Fertigungsprozesses integriert werden, in einem einzigen Prozess zu einer Baugruppe kombiniert werden. Um diesen neuartigen Engineeringprozess zu unterstützen, werden innovative Ansätze und Werkzeuge der Konstruktionsmethodik vorgestellt.
Keywords: 3D-Druck; Konstruktion; Produktentwicklung; MID; CAD; Elektronik; Mechatronik

Feasibility of Printed Optical Waveguides Over the Entire Process Chain by OPTAVER - Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Hamjah, Mohd Khairulamzari; Reitberger, Thomas; Zeitler, Jochen; Franke, Jörg; Lorenz, Lukas; Bock, Karlheinz; Backhaus, Carsten; Loosen, Florian; et al. (Springer International Publishing, 2022)
The integration of the knowledge of different engineering disciplines to build a three-dimensional optical short-range interconnect system is the core of this book. For this purpose, the physical and technological principles of optical technologies have to be considered. The focus here is on optical transmission technology. Attenuation, the propagation of optical signals, the construction of printed optical waveguides and their manufacturing processes play a special role. Likewise, product development methods of technical systems are a related field; since up to now, especially for 3D-Opto-MID, no adequate methodology exists. Analogies to mechatronic systems and their sub-processes do exist, but these have to be evaluated and expanded with regard to the new optomechatronic components.
CRIS-Team Scopus Importer:2024-12-16

Implementation of a Scattering Method for Rough Surfaces in a Raytracing Software linked with a CAD (Computer-Aided Design) Toolbox - Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert; Zeitler, Jochen; Franke, Jörg (Frontiers in Optics 2016, OSA Technical Digest (online) (Optical Society of America, 2016), paper FW3H.2, 2016)
The design and simulation of printed polymer optical waveguides is a new approach in the field of raytracing techniques, to link the CAD routines with the simulation process of the waveguides via raytracing methods.
Keywords: Polymer waveguides (130.5460); Propagating methods (220.2560); Scattering; rough surfaces (290.5880)

Integration of Semi-Automated Routing Algorithms for Spatial Circuit Carriers into Computer-Aided Design Tools - Zeitler, Jochen; Fischer, Christian; Goetze, Bernhard; Franke, Jörg (Electronics Circuit World Convention 13 (ECWC 13), 2014)
Though the market for 3D Molded Interconnect Device applications increases fast, the engineering process of these mechatronic assemblies still lag behind. The integration of electronic and mechanical design on mechatronic assemblies with complex spatial surfaces is a challenging task in the development process. This paper describes a method to create a MID specific product model that fulfills both requirements. This is on the one side the electrical design and on the other side the mechanical design. Both are considering design- and manufacturing rules, respectively keep-out areas. This product model is tied to two different mechanical computer-aided design systems, AutoCAD Inventor on the one side and Siemens NX on the other side. Furthermore the concept to flatten the 3D-circuitry, suitable for the surfaces of volume bodies, to ease 3D routing, will be discussed in this paper.
Keywords: MID; Design; CAD

Manufacturing of Polymer Optical Waveguides for 3D-Opto-MID: Review of the OPTAVER Process - Hamjah, Mohd Khairulamzari; Zeitler, Jochen; Eiche, Yannic; Lorenz, Lukas; Backhaus, Carsten; Hoffmann, Gerd Albert; Wienke, Alexander; Kaierle, Stefan; Overmeyer, Ludger; Lindlein, Norbert; Bock, Karlheinz; Franke, Jörg (2021 14th International Congress: Molded Interconnect Devices, MID 2021 - Proceedings, 2021)
In order to meet the increasing demand for data transmission over short distances of up to 100 m, the Optical Assembly and Connection Technology for ComponentIntegrated Bus Systems (OPTAVER) research group, funded by the German Research Foundation (DFG), developed a process for the additive manufacturing of three-dimensional optical waveguides. The research group focuses on design and modeling, simulation, and manufacturing polymer optical waveguides to produce 3D-Opto-Mechatronic-Integrated Devices (3D-Opto-MID). Inside 3D-Opto-MID, an optical coupler is presented based on an asymmetrical coupling principle. This paper reviews the entire process chain and the corresponding research results of the OPTAVER process.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 3D-Opto-MID; aerosol jet printing; asymmetrical optical bus coupling; flexographic printing; functionalization; printed multimode waveguides; Raytracing; wave propagation method

Manufacturing of polymer optical waveguides using self-assembly effect on pre-conditioned 3D-thermoformed flexible substrates - Hoffmann, Gerd-Albert; Wolfer, Tim; Zeitler, Jochen; Franke, Jörg; Suttmann, Oliver; Overmeyer, Ludger (Advanced Fabrication Technologies for Micro/Nano Optics and Photonics X, 2017)
Keywords: Optics; Design; Printing; Waveguide

Modeling, Simulation and Manufacturing of Polymer Optical Waveguides by Using the OPTAVER Process - Reitberger, Thomas; Zeitler, Jochen; Backhaus, Carsten; Hoffmann, Gerd-Albert; Wienke, Alexander; Lorenz, Lukas; Bock, Karlheinz; Wolter, Klaus-Jürgen; Suttmann, Oliver; Overmeyer, Ludger; Lindlein, Norbert; Franke, Jörg (Applied Industrial Optics: Spectroscopy, Imaging and Metrology 2019, 2019)
This paper shows the modeling, simulation and production of polymer optical waveguides using the OPTAVER process. The additive manufactured multimode waveguides with their typical cross-section of a circle shape are of low cost and high-performance.<br

Novel Approach for Implementation of 3D-MID Compatible Functionalities into Computer-Aided Design Tools - Zeitler, Jochen; Fischer, Christian; Goetze, Bernhard; Franke, Jörg (11th International Congress Molded Interconnect Devices, 2014)
Current Computer-Aided Design (CAD) tools offer a wide scope of functionality for design of mechatronic products. A number of electrical and mechanical CAD tools on the market fulfil demand in almost every application. Prevailing mechanical CAD tools offer besides simple geometric design also many advanced functionalities in the fields of Computer-Aided Engineering (CAE) or Manufacturing (CAM) to create for instance simulations for multi-physics or finite elements besides the simple shape design functionality. Electrical design tools on the other side contain part libraries for the schematic and geometric layout as well as automated routing algorithms with integrated design rule checks. Development within these two design tools often goes ahead simultaneously. However in the field of spatial electronic assemblies like 3D-MID (Moulded Interconnect Devices) a direct integration of the both disciplines is absolutely necessary. A 3D-MID application combines the conventional mechanical design and the electronic layout design on the same application. Therefore, for 3D-MID-design, ECAD (Electronic CAD) systems with the opportunity to create PCB layouts and MCAD (Mechanical CAD) systems with the functionality to design solid shapes have to be integrated into one single development environment. Existing tools allow import of geometrics from MCAD and schematics from ECAD to bring them together in the same environment. Nevertheless some specific functionalities like automated placement of conductor parts or the routing of tracks between them are still unsolved tasks. Due to the time consuming issue of these design domains a solution has to be found. Our research work has the goal to merge the advantages of ECAD and MCAD design instead of developing a completely new software environment. For that approach a layer model was generated, which connects the different software tools to a holistic picture. This should fulfil all requirements in the collaboration of electrical and mechanical design. Also technical restrictions like design and manufacturing rules have to be considered. Due to the nature of 3D-MID not only the electrical functionality is focussed but also the dependence with mechanical conditions. E.g. mechanical contact faces shouldn’t be permitted for electronic part placement or the routing of tracks. In order to realize all these functions a platform independent product model is created and implemented to generate a connection between these different systems and the implicit user knowledge. This product model builds a base for the routing and placement task of 3D-MID and further additional modules that can be implemented into the software structure to improve the scope of functionality. Within the current project that focusses a semi-automated routing, the user will be allowed to rip-up connections between the parts and to reroute with customized conditions by setting waypoints on the carrier surface. The routing will be semi-automated what means that not all connections will be routed at once to allow the user to have several options for the track planning. Finally, future challenges will be evaluated and further use of the results will be discussed in the paper.
Keywords: MID; Design; CAD; Routing

Novel approach for the implementation of 3D-MID compatible routing functionalities into computer-aided design tools - Zeitler, Jochen; Götze, Bernhard; Fischer, Christian; Franke, Jörg (Advanced Materials Research, 2014)
Molded Interconnect Devices can be considered as attractive option for the integration of electronic functions into mechanical systems. While development methods and procedures reached high standards, CAD tools still drag behind. This paper focusses the necessary software structure for implementing of automated routing algorithms or other MID specific extensions into CAD tools. An innovative three-layer model will be introduced and explained in detail. This paper also describes a method for mapping electrical components on unfolded surfaces for the further implementation of the automated routing algorithms.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 3D-ECAD; Design; Routing; Software development

Optical simulations of printed Polymer Optical Waveguides (POWs): search for their optical limitations caused by fabrication and application geometry - Backhaus, Carsten; Vögl, Christian; Zeitler, Jochen; Reitberger, Thomas; Lindlein, Norbert; Franke, Jörg (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, 2019)
Keywords: Polymer waveguides; Polymethyl methacrylate; Refractive index; Roughness; Surfaces; Systems design

Simulationsgestützte Produktionsplanung flexibler Fertigungssysteme - Selmaier, Andreas; Donhauser, Toni; Lechler, Tobias; Zeitler, Jochen; Franke, Jörg (wt Werkstattstechnik - Online, 2019)
While the behaviour of rigidly linked systems is relatively easy to model by means of material flow simulation, traditional simulation approaches are only suitable to a limited extent for flexible manufacturing systems due to the high data collection and parameterization effort. However, the use of real-time data can significantly improve the simulation of such systems. This paper presents an approach for simulation-based production planning of rapidly changing system
Keywords: simulation-based production planning; material flow simulation; realtime data

Technical Modelling Approach for Spatial Integrated Optomechatronic Products - Zeitler, Jochen; Reitberger, Thomas; Reichle, Andreas; Backhaus, Carsten; Lindlein, Norbert; Franke, Jörg (Procedia CIRP, Volume 84, 2019)
In the age of digitalization, the amount of data generated and transferred continues to increase dramatically. To increase the usability of this data it must be accessible with sufficient transmission bandwidth. Optical signals are already being used for transmitting data over long distances and high bandwidths, as this enables fast and low-loss data transmission. This trend is now also continuing in smaller scales of data transmission. Consequently, even highly integrated electrical circuits must be supported with optical components. Therefore, completely new research approaches for the product development of spatially integrated optical waveguides are necessary. The polymer-based aerosol jet printing represents a promising method to print optical waveguides on 3D circuit carriers. For this reason, the Research Group for Module Integrated Bus Systems deals with topics related to product development and production of such systems. A focus is to customize the design and associated modelling tasks accordingly. Thus, it is essential to create methodical approaches for a digital representation of waveguides and their production processes in order to map the physical behavior and to predict their manufacturability. Current studies show that integrated engineering approaches with removed boundaries among engineering domains are preferable to traditional engineering approaches. Consequently, novel engineering tools are needed for modelling the geometric as well as the physical properties of optical waveguides with the possibility to integrate specific design rule checks. The presented modelling approach in this paper provides/supports the creation of exact digital models without discontinuities through unnecessary interfaces. This article presents a method for a powerful computer-aided modelling environment that enables the design of models that are capable of representing and validating logical relationships among optoelectronic networks, but also considers challenges resulting from spatial geometric characteristics as well as restrictions from manufacturing and physic
Keywords: Computer aided design (CAD); Product development; Optomechatronics